Court and Country Politics in the Plays of Beaumont and Fletcher. - Finkelpearl, Philip J. (Princeton legacy library., 2014)
The seventeenth-century English collaborative authors Francis Beaumont and John Fletcher were not only the most popular playwrights of their day but also literary figures highly esteemed by the great critics of the age, Jonson and Dryden. Concentrating on the passions of the royalty and high nobility in a courtly atmosphere, their dramas are now usually seen as epitomizing a decadent turn in theater at the end of the Jacobean period. Philip Finkelpearl sets out to change this view by revealing the subtle political challenges contained in the plays and by showing that they criticize rather t.